A Study On Competitiveness of Sarawak Manufacturing Industries - Rossazana, Ab. Rahim; Rosita, Hamdan (Universiti Malaysia Sarawak, (UNIMAS), 2006)
This paper estimates the level of technical efficiency obtained from the Data Envelopment Analysis (DEA) approach using time series data of nineteen main industries in Sarawak’s manufacturing sector. DEA provides a mean of calculating apparent efficiency levels within a group of industries. The efficiency of an industry is calculated relative to the group’s observed best practice. The objective of this research is to examine the efficiency of manufacturing sector by determining the technical efficiency and the scale efficiency of the industries and to compare the composition as well as overall efficiency level among the industries. The paper is divided into three parts. First, it examined the overall efficiency level of nineteen main industries. Second, it compared the level of efficiency among the industries and lastly, it recommended some policy considerations that should be taken by the authorities concerned.